حقوق المعاقين وتطبيقاتها في السيرة النبوية : Rights of Disabled and its application in the biography of the Holy Prophet PBUH - Musannif shah, musannifshah; Iftikhar Hussain, iftikharhussain (Al Manhal Research Journal, 2021)
Islam being a perfect religion covers all spheres of human life: social , political and economics. It provides guidance in every field of life, so that people would find it helpful in their daily affairs. The relation between rights and duties has been explained in such a matchless manner that no ambiguity remains there. The farewell sermon of the Holy prophet PBUH is a corner stone to understand the value of human rights. Islam has contributed comprehensively to uplift the rights of poor and weak elements of the society while praising their status particularly in the context of Arab history where no concept of rights existed. The world has failed to produce a document, which guarantees more equitable rights in such unequivocal manner as Islam did. The Holy prophet PBUH showed great concerned to ensure the basic rights of disabled person and he did his best to maintain their dignity and self-respect so that they could achieve their basic rights of education, equality, inheritance and debate. The prophet of Islam visited them frequently to empathize with them and gave them maximum relaxation in their religious duties and even sometime exempted them.This article presents the evidence and special attention of the holy prophet PBUH to the disabled persons and their rights from the life of the holy prophet. At the end , the researchers have drawn different results.